Environmental mutations in the Campo focus challenge elimination of sleeping sickness transmission in Cameroon. Issue 3 (20th May 2022) - Melachio Tanekou, Tito Tresor; Bouaka Tsakeng, Calmes Ursain; Tirados, Inaki; Torr, Steve J.; Njiokou, Flobert; Acho, Alphonse; Wondji, Charles Sinclair
Abstract: Sleeping sickness is still prevalent in Campo, southern Cameroon, despite the efforts of World Health Organization and the National Control Programme in screening and treating cases. Reducing disease incidence still further may need the control of tsetse vectors. We update entomological and parasitological parameters necessary to guide tsetse control in Campo. Tsetse flies were trapped, their apparent densities were evaluated as the number of flies captured per trap per day and mapped using GIS tools. Polymerase chain reaction based methods were used to identify their trypanosome infection rates. Glossina palpalis palpalis was the dominant vector species representing 93.42% and 92.85% of flies captured respectively during the heavy and light dry seasons. This species presented high densities, that is, 3.87, 95% CI [3.84–3.91], and 2.51, 95% CI [2.49–2.53] flies/trap/day in the two seasons. Moreover, 16.79% (of 1054) and 20.23% (of 1132 flies) were found infected with at least 1 trypanosome species for the 2 seasons respectively, Trypanosoma congolense being the most prevalent species, and Trypanosoma . brucei gambiense identified in 4 samples. Tsetse flies are abundant in Campo and present high trypanosome infection rates. The detection of tsetse infected with human trypanosomes near the newly created palm grove show workers' exposition. Tsetse densities maps built will guide vector control with 'Tiny Targets'. Abstract : High densities of tsetse fly vectors of Human sleeping sickness and animal trypanosomoses are recorded in the transborder focus of Campo, South Cameroon. Around 20% of these flies are infected with trypanosome parasites, among which Trypanosoma brucei gambiense, the human parasite. Population activities and new development projects implemented in the area (plantations creation, roads…) increase human exposure to tsetse bites and disease transmission risk, and therefore, vector control is needed.